Pediatric Burns from Glass-Fronted Fireplaces in Canada: A Growing Issue Over the Past 20 Years. Issue 5 (September 2016) - Toor, Jay; Crain, Jennifer; Kelly, Charis; Verchere, Cindy; Fish, Joel
Abstract : There is an alarming lack of public awareness surrounding the safety of glass-fronted fireplaces. This has resulted in an active campaign from the American Burn Association Prevention Committee. One issue encountered while advocating for prevention among manufacturers is the lack of corroborating and accurate data. The purpose of this study was to examine the annual trends and epidemiology of glass-fronted fireplace-related burn injuries to children less than 15 years old, who presented to Canadian emergency departments between 1990 and 2010. Records of pediatric burn injuries related to glass-fronted fireplaces were extracted from the Canadian Hospitals Injury Reporting and Prevention Program database for the study period (1990–2010). Cases were analyzed in terms of anatomic area affected, demographics, seasonality, safety device use, and injury severity. A total of 616 cases of burns from glass-fronted fireplaces were identified. The incidence increased at an average of 2.7 cases per year. This is a greater than 20-fold increase over 20 years. Seventy-five percentage of the cases occurred in children less than 2 years, and 95% occurred in children less than 5 years. The study demonstrated a growing risk from glass-fronted fireplace burns, likely due to the increasing popularity of household gas fireplace units. These units are a particular risk to children less than 2 years, attributable to their developing mobility and reduced reaction time. This is a preventable injury that should be addressed through changes to legislation and manufacturing.